Rural political participation in the United States: alienation or action?. Issue 2 (4th May 2019) - Kaufman, Chelsea N.
ABSTRACT: Globally, concern has risen over support for authoritarian populism, in some cases specifically among rural populations. Rural influence, however, may be limited by relatively low political participation. This article examines participation in the United States, where past evidence shows rural Americans have been less involved in politics than their urban counterparts. Analysis of American National Election Studies (ANES) data from 1952 to 2012 shows historically less participation for rural residents relative to suburban and urban residents. Between 1988 and 2008, low political trust, a negative economic outlook, high external efficacy, and being more ideological and partisan are associated with increased political participation. These findings imply rural Americans with polarised views who feel deprived of political and economic power may participate more frequently in future political activities. Concurrently, similarly polarised circumstances in urban areas and low rural political efficacy may lead the rural-urban participation gap to persist.